Peningkatan Pemahaman Siswa Kelas V Terhadap Konsep Perubahan Wujud Benda Tema 7 Subtema 2 Dengan Metode Eksperimen Di SDN 01 Taman - Mutmainah, Siti; Tryanasari, Dewi; Jatmikawati, Melina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is one of the crucial factors in the growth of a nation. According to this idea, it is necessary to make efforts to improve the quality of the learning process, especially in understanding the concept of changes in the form of objects by carrying out classroom action research with the aim of improving the quality of students' learning in various aspects, especially in efforts to increase students' understanding using experimental methods. This classroom action research was carried out in two learning cycles using each cycle consisting of planning, implementation, observation, assessment and reflection. during the research in March in class V of SDN 01 Taman Kota Madiun, with a total of 28 students. The data collection methods used are qualitative data and quantitative data. Based on the research, it can be concluded that the experimental method can increase the understanding of class V students at SDN 01 Taman regarding the concept of changes in the form of objects, which is proven by increasing the percentage of student learning test results in cycle I of 67.50%, which is higher in cycle II of 85.50%.